PWWP domain-containing protein Crf4-3 specifically modulates fungal azole susceptibility by regulating sterol C-14 demethylase ERG11 - Pengju Yu; Shuting Ye; Mi Zhou; Long Zhang; Zhongchi Zhang; Xianyun Sun; Shaojie Li; Chengcheng Hu (mSphere)
ABSTRACT The widespread use of azole antifungals in agriculture and clinical settings has led to serious drug resistance. Overexpression of the azole drug target 14α-demethylase ERG11 (CYP51) is the most common fungal resistance mechanism. However, the presence of additional regulatory proteins in the transcriptional response of erg11 is not yet fully elucidated. In this study, leveraging the identified key promoter region of erg11 that controls its response to azoles in Neurospora crassa, we pinpointed a protein, Crf4-3, which harbors a PWWP domain and exerts a positive regulatory influence on azole resistance, as determined by DNA pulldown assays. The removal of Crf4-3 results in heightened sensitivity to azoles while remaining unaffected by other stressors tested. Additionally, the deletion leads to the abolition of transcriptional responses of genes such as erg11 and erg6 to ketoconazole. Interestingly, the basal expression of erg1, erg11, erg25, and erg3A is also affected by the deletion of crf4-3, indicating its role in sterol homeostasis. Crf4-3 homologs are broadly distributed across the Pezizomycotina fungi. The gene deletion for its homologous protein in Aspergillus fumigatus also significantly improves sensitivity to azoles such as voriconazole, primarily through the attenuation of the transcriptional response of erg11. Our data, for the first time, identified Crf4-3 as a novel regulatory protein in the azole stress response of filamentous fungi, offering fresh insights into the mechanisms of azole resistance.IMPORTANCETranscriptional control of pivotal genes, such as erg11, stands as the primary driver of azole resistance. Although considerable effort has been dedicated to identifying transcription factors involved, our knowledge regarding the use of transcriptional regulation strategies to combat azole resistance is currently limited. In this study, we reveal that a PWWP domain-containing protein Crf4-3, which is conserved in Pezizomycotina fungi, modulates fungal azole sensitivity by transcriptionally regulating sterol biosynthetic genes, including erg11. These results also broaden the understanding of fungal PWWP domain-containing proteins regarding their roles in regulating resistance against azole antifungals. Considering research on small molecules targeting the PWWP domain in humans, Crf4-3 homolog emerges as a promising target for designing fungal-specific drugs to combat azole resistance.